1983
DOI: 10.1002/cpa.3160360503
|View full text |Cite
|
Sign up to set email alerts
|

The small dispersion limit of the korteweg‐de vries equation. ii

Abstract: In Part I* we have shown, see Theorem 2.10, that as the coefficient of uxxx tends to zero, the solution of the initial value problem for the KdV equation tends to a limit u in the distribution sense. We have expressed u by formula (3.59), where ψx is the partial derivative with respect to x of the function ψ* defined in Theorem 3.9 as the solution of the variational problem formulated in (2.16), (2.17). ψ* is uniquely characterized by the variational condition (3.34); its partial derivatives satisfy (3.51) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 8 publications
(4 reference statements)
3
165
0
1
Order By: Relevance
“…We should define the time evolution for the multivalued functions. (The same conclusion may be deduced from the results of Lax, Levermore and Venakides [32,33].) We constructed in the works [18,19] the class of special 1-and 3-valued functions for the investigation of stability of the "dispersive shock wave" which should be realized also as the asymptotics t → ∞.…”
Section: Integrability Of the Hamiltomian Ht Systemssupporting
confidence: 56%
“…We should define the time evolution for the multivalued functions. (The same conclusion may be deduced from the results of Lax, Levermore and Venakides [32,33].) We constructed in the works [18,19] the class of special 1-and 3-valued functions for the investigation of stability of the "dispersive shock wave" which should be realized also as the asymptotics t → ∞.…”
Section: Integrability Of the Hamiltomian Ht Systemssupporting
confidence: 56%
“…15 What is intriguing is this: suppose we keep h as an arbitrary, nonzero parameter and solve ͑15͒ analytically, using the inverse scattering method, we obtain a function u h ͑x , t͒. In the work of Lax and Levermore, 16 it was shown that in the zero-dispersion h → 0 limit, the sequence u h ͑x , t͒ does not converge to a solution of Burgers' equation ͑17͒. Therefore, we conclude that the h Ͼ 0 continuum model allows fundamentally different phenomena than the h = 0 model.…”
Section: Remark 1: Zero-dispersion Casementioning
confidence: 99%
“…This method is a natural generalization of the Kay-Moses determinant [6] and its expansion by Lax-Levermore [7]. We recall that (2.8) Formula (2.7) can be generalized formally in three ways to give more solutions to the KdV equation.…”
Section: The Explicit Solutionmentioning
confidence: 99%